Artificial intelligence in parasitological diagnosis and article writing - Bastidas , Gilberto (2026)
Parasitic diseases are widespread and highly prevalent worldwide, and are therefore considered a serious public health problem. This situation is further exacerbated by the compromised sensitivity and specificity of diagnostic methods based on the analysis of host organic samples by experts in the field. The objective is to present general arguments regarding artificial intelligence in parasitological diagnosis and in the writing of articles in this field of knowledge. The potential of artificial intelligence as a diagnostic tool in parasitology is enormous, but not so much so in the writing of scientific articles, which still requires human reasoning in several aspects. In parasitic diseases, artificial intelligence saves physicians time and increases the efficiency of the diagnostic and treatment workflow, and reduces observer bias in sample analysis.